Political Risk and Real Exchange Rate: What can we Learn from Recent Developments in Panel Data Econometrics for Emerging and Developing Countries? - Mohsen Bahmani-Oskooee; Thouraya Hadj Amor; Ridha Nouira; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper focuses on the analysis of the long-run response of the Real Exchange Rate (RER) to political risks and tests whether non-economic variables have an impact on RER in 31 emerging and developing countries. We use annual data from the International Country Risk Guide database over the 1984 to 2016 period. Based on the recently developed method of Cross- Sectionally Augmented ARDL approach of Chudik and Pesaran (2015b), and the panel threshold estimation of Chudik et al. (2017) our main findings are the following: i) countries experiencing a high degree of corruption, a high risk to investment, or a high degree of political instability tend to experience a real exchange rate depreciation, ii) there exists strong evidence for a threshold effect on the relationship between investment profile-RER, corruption-RER and political instability-RER. Specifically, political instability and corruption adversely affect real exchange rate especially when they exceed the threshold. iii) the effects of bureaucracy, law, and order seem to be statistically insignificant on the RER. Our findings are robust to the inclusion of the Balassa-Samuelson effect in the estimated equations.
Keywords: C21; D73; F31; P48; 330; real exchange rate; political instability; institutional quality; cross-sectionally augmented ARDL; threshold effects; emerging and developing countries